2021
DOI: 10.14260/jemds/2021/96
|View full text |Cite
|
Sign up to set email alerts
|

Study of Platelet Indices and Their Interpretation in Thrombocytopenia in a Tertiary Care Hospital

Abstract: BACKGROUND Thrombocytopenia may either be due to increased destruction or impaired production of platelets. Platelet count alone is not enough to determine the mechanism of low platelets. Platelet indices like mean platelet volume (MPV), platelet distribution width (PDW), platelet large cell ratio (P-LCR) and platelet crit (PCT) can help determine the cause and we aimed at finding their role and function in cases of thrombocytopenia. METHODS An observational cross-sectional study of 155 patients with thromboc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Grade 1 thrombocytopenia is most frequent (47%) followed by grade 2 (24%), grade 3 (15.0%) and grade 4 (14%). In a similar study done by Mittal V et al [10] classified thrombocytopenia into three categories: mild thrombocytopenia (platelet count 100 to 150 x 10 9 / L), moderate thrombocytopenia (platelet count > 50 x 10 9 / L and 100 x 10 9 / L), and severe thrombocytopenia (platelet count less than 50 x 10 9 / L). Mild thrombocytopenia was the most common type, followed by moderate and severe thrombocytopenia.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Grade 1 thrombocytopenia is most frequent (47%) followed by grade 2 (24%), grade 3 (15.0%) and grade 4 (14%). In a similar study done by Mittal V et al [10] classified thrombocytopenia into three categories: mild thrombocytopenia (platelet count 100 to 150 x 10 9 / L), moderate thrombocytopenia (platelet count > 50 x 10 9 / L and 100 x 10 9 / L), and severe thrombocytopenia (platelet count less than 50 x 10 9 / L). Mild thrombocytopenia was the most common type, followed by moderate and severe thrombocytopenia.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, Male preponderance was observed similar to other studies (M:F-1.4: 1 ). Mittal V et al [10] did a study on patients aged 1 to 80 years old and found that 65 percent of the patients were male and 35 percent were female. Francis et al [11] found 61.2% male and 38.8% female patients, with a male to female ratio of 1.57:1.…”
Section: Discussionmentioning
confidence: 99%
“…sex, ethnicity etc., (2). Platelet indices include: PDW, MPV, PCT and P-LCR which are used to determine cases of thrombocytopenia (3). In children, urinary tract infection (UTI) is most common disease caused by bacterial infections which could lead to severe morbidity and mortality (4).…”
Section: Introductionmentioning
confidence: 99%